PARADIGMA SOSIOLOGI DALAM ILMU DAKWAH (Perspektif Pemikiran Al-Ghozali) - Binti, siti (KOMUNIKA, 2018)
The religion that is manifested in people's lives is a social fact. As a social fact, religion is studied by sociologists using a scientific approach. The discipline of science used by sociologists in studying religious societies is called the Sociology of Religion. In a sociological perspective, religion is seen as a belief system that is manifested in certain social behaviors. It is related to human experience, both as individuals and groups, so that every behavior that is portrayed will be related to the belief system of the religious teachings that it adopts. Individual and social behavior is driven by internal forces based on religious teachings that internalize before. In this case the author relates to Islamic da'wah so that it can be found that preachers as religious broadcasters use a sociological approach to religion to spread the call to obtain perfection in religion.